2022
DOI: 10.1139/cjfr-2021-0041
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different planting configurations and clones on biomass and carbon storage of a 12-year-old poplar ecosystem in southern China

Abstract: The main objective of this study was to compare the effects of two densities (278 stems·ha−1 with two spacings of 6 m × 6 m or 4.5 m × 8 m, 400 stems·ha−1 with two spacings of 5 m × 5 m or 3 m × 8 m) and three poplar clones (NL95, NL895, and NL797) on productivity and carbon (C) sequestration of poplar ecosystems. The results showed that planting density significantly affected the biomass of a single tree. The mean tree biomass of clone NL95 was higher in all spacings than that of the other clones, with a sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 57 publications
(34 reference statements)
2
3
0
Order By: Relevance
“…Tree height, DBH, and AGB I were influenced by spacing such that each of these variables tended to increase as the spacing or area available to the tree increased. Consistent with the growth of poplars in other studies, height was mildly responsive to spacing while DBH and AGB I were considerably responsive [40,41,61,62]. Fang et al [63], who worked in the Jiangsu Province of China, confirmed genetic control over the correlation between DBH and crown volume for 14 eastern cottonwood clones native to the southeastern United States, but they also recognized the strong impact of environment on this relationship.…”
Section: Cottonwood Survival and Growth Relative To Spacing On A Degr...supporting
confidence: 64%
See 4 more Smart Citations
“…Tree height, DBH, and AGB I were influenced by spacing such that each of these variables tended to increase as the spacing or area available to the tree increased. Consistent with the growth of poplars in other studies, height was mildly responsive to spacing while DBH and AGB I were considerably responsive [40,41,61,62]. Fang et al [63], who worked in the Jiangsu Province of China, confirmed genetic control over the correlation between DBH and crown volume for 14 eastern cottonwood clones native to the southeastern United States, but they also recognized the strong impact of environment on this relationship.…”
Section: Cottonwood Survival and Growth Relative To Spacing On A Degr...supporting
confidence: 64%
“…Evaluated against some other reports for poplars raised in SRWC systems across the temperate zone, early AGC stocks at our study site appear underwhelming [39,41,65,71]. The AGC stocks calculated for an eastern cottonwood planting spaced 3.7 × 3.7 m in Issaquena County, MS, USA, reveal that the similarly spaced stands at our study site accumulated 28.5 Mg ha −1 less carbon by year 10 [55].…”
Section: Stand Development and Dynamics Of Carbon Accumulationsupporting
confidence: 60%
See 3 more Smart Citations